HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG HIPERTENSI DALAM KEHAMILAN TERHADAP RESIKO PREEKLAMSIA BERAT - Ester Simanullang (Excellent Midwifery Journal, 2019)
Hypertension is the increase in systolic blood  pressure above 140 mmHg and diastolic above  90 mmHg. Hypertension often causes changes in blood vessels that can  lead  to increasing blood  pressure. Today people prefer to choose  ready meals are generally very low in fiber, high in fat and salt mengandum  lost. The public should be aware that taking makanana above can  lead  to hypertension. So for people who have suffered or are expected to organize their daily diet. Regulate diet but to draw up the frequency of  food  consumption, food  habits, consumption of drinks, the portion size and qulity of food daily. Research  aims to determine the aattitude of  the attitude of the mother of  hypertension  on the incidence of pre-eclampsia. The study design was descriptive. Respondents in this study were pregnant women  who have hypertension and pre-eclampsia in the People’s Health Center Island Asahan number of 30 respondents. Sampling of this research is total sampling. Collecting data in this study using a questionnaire designed by researcher and distributed  to the respondents. Whereas the data analysis using Chi-square statistical test with a cinfidence  level of  95% (α = 0,05). The results showed no relationship between  knowledge and attitude of pregnant women about hypertension on the incidence of pre-eclampsia with a value of 0.001 (<0.05). Keywords        : Knowledge attitude, hypertension and pre-eclampsia